Development of risk and hazard maps for floods in localities on Chilia Branch - CONSTANTINESCU Adrian (Scientific Annals of the Danube Delta Institute, 2017)
The paper meets the requirements of Directive 2007/60 / EC of the European Parliament and Council from 23 October 2007 on the assessment and management of flood risks, namely making hazard maps and flood risk maps at individual river basin scale detailed for localities on Chilia branch: Patlageanca, Sălceni, Ceatalchioi, Plauru, Pardina, Chilia Veche and Periprava. The designed hydraulic scenarios simulate real situations with breaches in the protective embankment of a width of 20m for 1 day. In total, were made 33 scenarios starting from the minimum to the maximum flooding levels with a step of increasing the water level at 25cm. Based on flood hazard maps, there were also made flood risk maps using the vulnerability curves for the analyzed categories: buildings, agriculture, road, forest, grassland.